Rebuilding Social Capital in Post-Conflict Societies: A Women-Centered Perspective The Case of Darra Adamkhel - Saiqa Bibi; Muhammad Zakriya (Journal of Religion and Society, 2025)
This study explores the transformation of women's status and their contribution to rebuilding social capital in the post-conflict context of Darra Adamkhel, Khyber Pakhtunkhwa, Pakistan. Using a qualitative approach, in-depth interviews and focus group discussions (FGDs) were conducted with women from different age groups and educational backgrounds. Findings reveal that while patriarchal norms continue to limit women's mobility, education, and economic participation, notable shifts have occurred in women's roles, agency, and decision-making. Women have increasingly accessed education, entered the workforce, and engaged in social decision-making processes. However, deeply rooted traditions such as arranged, cousin, and underage marriages persist, as do gender-based restrictions and practices like honour killing. The role of women stood positively changed particularly their access to education which is a good gesture towards their empowerment. However, they showed concern regarding their direct participation in important matters and jirgas‘ decisions about them. They complained of no share in coal profit distribution and division of property. The strong clutches of patriarchy, conservation and orthodoxy about local women started getting loosen. They were still in favour of preferential, early and arranged marriages, with opposition from students of both genders. The elderly women of Darra Adamkhel favoured the practices of the past, but conversely the youngsters particularly the educated ones supported the merger of FATA and changes occurred after the conflict. Female Student's response was positive towards changes in the region. The study recommends creating a conflict-free situation in the area towards speedy development of the area and reconstruction of the damaged educational institutes on priority basis to provide the education to the women. The paper argues that empowering women in post-conflict societies is central to rebuilding social capital and fostering sustainable peace. Keywords: Social Capital, Post-Conflict Reconstruction, Women’s Empowerment, Darra Adamkhel, Gender, Militancy